The future of emissions trading. (27th June 2014) - Meckling, Jonas
<x xml:space="preserve">Abstract</x> Over the past 15 years, carbon markets have been set up by private and public actors at various geographic scales and with varying financial scope. The history of the early stage of carbon markets reveals a mixed record: the instrument diffused widely across the globe, while existing carbon markets performed rather slow, though anecdotal evidence suggests positive side effects on climate policymaking. Going forward, three key driving forces are likely to shape the future of emissions trading: (1) the source and sustainability of political demand for climate action in general and carbon markets in particular, (2) the governance of operating carbon markets including questions of bureaucratic capacity and regulatory capture, and (3) the pattern of market globalization, which encompasses issues of carbon price comparability, market linkage, and expansion. Depending on how these driving forces and fault lines play out, a number of scenarios are possible, ranging from strongly embedded and effective carbon markets to their collapse. The trajectory to any one of these scenarios could be characterized by tipping points, which are likely to come about incrementally. WIREs Clim Change 2014, 5:569–576. doi: 10.1002/wcc.293 For further resources related to this article, please visit the WIREs website. Conflict of interest: The author has declared no conflicts of interest for this article.